Profile of nonstructural glycoprotein NS1 as a diagnostic marker in dengue type 2 virus infection - Muliawan, Sylvia Y. (Universa Medicina, 2007)
BackgroundSeveral studies in dengue on cloned or cell culture passaged in wild and attenuated virus have been performed, but each report described different sites of nucleotide and amino acid changes possibly associated with virulence. The aim of this study was to investigate protein expression of dengue type 2 virus infected C6/36 cells through two-dimensional gel electrophoresis followed by N-terminal Edman degradation sequencing to identify target proteins.MethodsTwo type of samples; dengue type 2 virus-infected C6/36 cells and uninfected C6/36 cells were prepared. Immobilized non-linear pH gradient strips, pH 3-10 were used in isoelectric focusing, and 10% homogeneous gels were used in Sodium dodecyl sulphate - Polyacylamide gel electrophoresis. The target protein spots were subsequently transferred onto polyvinyldifluoride membrane by western blotting and visualized by coomassie brilliant blue for N-terminal sequencing purpose.ResultsThis study revealed four target protein spots in dengue type 2 virus-infected C6/36 cells that were not present in uninfected C6/36 cells. The N-terminal sequencing result was D-S-G-C-V-V-S-W-K-N-K which was identical to nonstructural glycoprotein NS1 (Swissprot-database) associated with the replication process of flaviviruses. ConclusionNonstructural NS1 might be used as a diagnostic marker and/or as a parameter to evaluate the effect of antiviral agents for dengue type 2 virus infection/replication.